### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

fib(0) → 0
fib(s(0)) → s(0)
fib(s(s(x))) → +(fib(s(x)), fib(x))
+(x, 0) → x
+(x, s(y)) → s(+(x, y))

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(2n):
The rewrite sequence
fib(s(s(x))) →+ +(fib(s(x)), fib(x))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [x / s(x)].
The result substitution is [ ].

The rewrite sequence
fib(s(s(x))) →+ +(fib(s(x)), fib(x))
gives rise to a decreasing loop by considering the right hand sides subterm at position [1].
The pumping substitution is [x / s(s(x))].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
fib, +'

They will be analysed ascendingly in the following order:
+' < fib

### (8) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

Generator Equations:
gen_0':s2_0(0) ⇔ 0'
gen_0':s2_0(+(x, 1)) ⇔ s(gen_0':s2_0(x))

The following defined symbols remain to be analysed:
+', fib

They will be analysed ascendingly in the following order:
+' < fib

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)

Induction Base:
+'(gen_0':s2_0(a), gen_0':s2_0(0)) →RΩ(1)
gen_0':s2_0(a)

Induction Step:
+'(gen_0':s2_0(a), gen_0':s2_0(+(n4_0, 1))) →RΩ(1)
s(+'(gen_0':s2_0(a), gen_0':s2_0(n4_0))) →IH
s(gen_0':s2_0(+(a, c5_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

Lemmas:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)

Generator Equations:
gen_0':s2_0(0) ⇔ 0'
gen_0':s2_0(+(x, 1)) ⇔ s(gen_0':s2_0(x))

The following defined symbols remain to be analysed:
fib

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
fib(gen_0':s2_0(+(1, n421_0))) → *3_0, rt ∈ Ω(n4210)

Induction Base:
fib(gen_0':s2_0(+(1, 0)))

Induction Step:
fib(gen_0':s2_0(+(1, +(n421_0, 1)))) →RΩ(1)
+'(fib(s(gen_0':s2_0(n421_0))), fib(gen_0':s2_0(n421_0))) →IH
+'(*3_0, fib(gen_0':s2_0(n421_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

Lemmas:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)
fib(gen_0':s2_0(+(1, n421_0))) → *3_0, rt ∈ Ω(n4210)

Generator Equations:
gen_0':s2_0(0) ⇔ 0'
gen_0':s2_0(+(x, 1)) ⇔ s(gen_0':s2_0(x))

No more defined symbols left to analyse.

### (15) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)

### (17) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

Lemmas:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)
fib(gen_0':s2_0(+(1, n421_0))) → *3_0, rt ∈ Ω(n4210)

Generator Equations:
gen_0':s2_0(0) ⇔ 0'
gen_0':s2_0(+(x, 1)) ⇔ s(gen_0':s2_0(x))

No more defined symbols left to analyse.

### (18) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)

### (20) Obligation:

TRS:
Rules:
fib(0') → 0'
fib(s(0')) → s(0')
fib(s(s(x))) → +'(fib(s(x)), fib(x))
+'(x, 0') → x
+'(x, s(y)) → s(+'(x, y))

Types:
fib :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
+' :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
gen_0':s2_0 :: Nat → 0':s

Lemmas:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)

Generator Equations:
gen_0':s2_0(0) ⇔ 0'
gen_0':s2_0(+(x, 1)) ⇔ s(gen_0':s2_0(x))

No more defined symbols left to analyse.

### (21) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':s2_0(a), gen_0':s2_0(n4_0)) → gen_0':s2_0(+(n4_0, a)), rt ∈ Ω(1 + n40)